Donepezil ameliorates oxaliplatin-induced peripheral neuropathy via a neuroprotective effect - Takehiro Kawashiri; Shiori Shimizu; Nao Shigematsu; Daisuke Kobayashi; Takao Shimazoe (Elsevier, 2019)
Oxaliplatin induces severe peripheral neuropathy. The effect of donepezil, a drug used for treatment of Alzheimer's disease, on oxaliplatin-induced peripheral neuropathy was investigated using both in vivo and in vitro models. Donepezil effectively attenuated oxaliplatin- and cisplatin-induced inhibition of neurite outgrowth in cultured PC12 cells. In a rat model, repeated oral administration of donepezil (5 times/week for 4 weeks) ameliorated oxaliplatin-induced mechanical allodynia (von Frey test) and sciatic nerve axonal degeneration. Moreover, donepezil did not inhibit the anti-tumor activity of oxaliplatin in any cultured cancer cell line. Therefore, donepezil may be useful for managing oxaliplatin-induced peripheral neuropathy. Keywords: Donepezil, Oxaliplatin, Peripheral neuropathy